The Quality of Delegated Regulations in the Job Creation Law - Achmad Safiudin; Riza Multazam Luthfy; Airin Liemanto (NEGREI: Academic Journal of Law and Governance, 2025)
The existence of Delegated Regulations in the Job Creation Law is crucial for the proper implementation of the law. However, the excessive number of delegated regulations, created in a short time without in-depth study, has led to various problems in their implementation. This article captures the dynamics of delegated regulations under the Job Creation Law, assesses their quality, and formulates an ideal oversight model for their formation. This research is a normative legal study that analyzes in detail the concept of delegated regulations and the supervision of Government Regulations and Presidential Regulations as delegated regulations under the Job Creation Law, through three approaches: the statutory regulatory approach, the conceptual approach, and the comparative approach. Legal materials are reviewed and analyzed in depth. Historically, the dynamics of delegated regulations in the Job Creation Law are divided into three periods: after the enactment of Law 11/2020, after the Constitutional Court Decision Number 91/PUU-XVIII/2020, and after the enactment of Law 6/2023 on Job Creation. The dynamics of public rejection of the Job Creation Law's formation have not prevented the government from continuing to issue delegated regulations under it. This has led to numerous weaknesses in the delegation regulations, including their hasty creation (approximately 3 months), excessive government authority, and oversight issues. Therefore, oversight by both the executive and legislative branches, similar to the concepts in Australia and the United Kingdom, is necessary to improve the quality of the delegation regulations.